Creating an Embodied Phenomenological Typology for Describing the Qualitative Experience of Traumatic Space from Continued Bombings. Issue 5 (18th August 2019) - Goshen, Ilai; Huss, Ephrat; Koch, Sabine C.
Abstract: The effect of ongoing bombs and sirens in civilian areas and in day-to-day life, as is typical in current war situations, transforms the spaces of everyday living into traumatic spaces. Not only do the spaces hold memories of past traumas, but they are also stages for trauma that will occur in the near future. Thus, the most familiar "safe spaces" of life—my room, my house, my street, my suburb—become infused with traumatic memories. While there is literature on defining and measuring traumatic experience, there is less descriptive literature concerning how people experience their embodied and immediate space in such contexts. How do people experience the shift of familiar spaces around them to violent and chaotic spaces from a phenomenological and embodied standpoint? This view takes trauma out of the body as disconnected from context and situates body in environment, figure within background. This research focused on the spatial experiences in vignettes of bombing experiences of 24 mothers diagnosed with PTSD in an ongoing war context. It created a typology of four axes of spatial experiences of this traumatic space including horizontal organization of space, vertical organization of space, close and distant elements, and inside–outside elements. The findings show how spatial narratives of civilian bombing may aid in unraveling fragmented traumatic memories of local spaces where the bombing occurred, and in this way, help to reconstruct its safety. We thus enable a narrative of the spatial elements of the event that utilizes spatial concepts rather than abstract or feeling concepts within the body, decontextualized from the physical surroundings. This research aims to contextualize traumatic experience within familiar and local spaces to investigate how this perspective may support trauma narration as part of the healing process.